Cybersecurity in property digitisation: a taxonomy and evaluation of current security methods - Anuradha Uppar; Nagaveni Veerakyatharayappa; Parvathi Chikkanna (Institute of Advanced Engineering and Science, 2026)
The proliferating methods of digitization for documents related to real estate, land, property, and tax, encountered with critical security challenges. Such documents, which have an inclusion of high-value information, such as transaction history, geographic boundaries, tax assessment, and ownership details, are quite prime targets for various types of cyber threats. It is observed that with security domains advancing in faster pace, their implications towards securing such legal documents are questionable, especially in the presence of emerging lethal threats. This manuscript presents a comprehensive and highly compact exhibit of curated information about the effectiveness of all identified security solutions. The presented study has discussed the taxonomy of six mechanisms of securing property-related digitized document. It was found that although the impersonation attacks and forgery can be addressed with multifactor authentication, digital signatures and blockchain, they are not reportedly found to be mitigating modern-day threats like social engineering, and insider collusion. The outcome of this study infers that hybrid approaches fusing with zero-trust models, anomaly detection, and artificial intelligence (AI) demands more resilient security system. The paper contributes towards some novel findings of widely deployed security solutions, research trends, and gaps which will offer definitive guidelines towards designing a novel solution.